Inoculation of ceratocystis fimbriata ellis & halsted in eucalyptus spp. And evaluation pf genetic diversity by issr markers - Gomes, Caio Augusto Fidelix Carneiro; Pereira, Fernanda Bortolanza [UNESP]; De Oliveira Garcia, Flávio Augusto; Garret, Alexandre Techy De Almeida; De Siqueira, Leandro; Tambarussi, Evandro Vagner (Instituto de Pesquisa e Estudos Florestais (IPEF), 2019)
Ceratocystis fimbriata is the wilt-causing fungus in a wide range of hosts. The fungus develops through the vascular system and is autochthonous of the soil, so that the search for resistant genotypes is one of the few viable control strategies. Thus, the objective of this research was to study the behavior of species of the genus Eucalyptus after the inoculation with two C. fimbriata isolates. The experiment was carried out in a completely randomized design (DIC), in a factorial scheme (hosts x isolates). The disease severity evaluation was based on the lesion extension in the stem of three Eucalyptus species seedlings at 190 days of age, after 40 days from inoculation. Within each species, six individuals were classified into subgroups for severity level and evaluated by eight ISSR markers. Only Eucalyptus nitens differed statistically regarding the severity observed in relation to the other species. In all the species, the isolates were able to cause disease when we compared inoculated plants to control plants. We observed a higher fixation index within the subgroups (0.26) when compared to the species (0.15) ones, indicating a greater genetic diversity within the evaluated species. The markers used were able to differentiate plants that presented higher and lower severity, showing that the selection assisted by molecular markers can be a viable alternative for the breeder.
Inoculacąõ de ceratocystis fimbriata ellis & halsted em eucalyptus spp. e avaliacąõ da diversidade genética por marcadores issr
Keywords: Ceratocystis-wilt; Issr; Marker assisted selection